Clinical evaluation of a water-in-oil emulsion with protective and regenerative properties for the anogenital area - Küppers V; Kemper M; Abels C (Dove Medical Press, 2015)
Volkmar Küppers,1 Michael Kemper,2 Christoph Abels2 1Gynecological Practice, Dysplasia-Clinic, Düsseldorf, Germany; 2Dr August Wolff GmbH & Co KG Arzneimittel, Bielefeld, Germany Abstract: Inadequate hygiene, aggressive cleansing, and chafing skin folds, as well as urine, feces, and sweat may trigger irritative contact dermatitis in the anogenital area. Serious recommendations for protection of the skin toward irritants include hygienic aspects and the use of appropriate skin care. Furthermore, preventing an accumulation of irritants on unprotected skin is mandatory. An intraindividual comparison study with 30 participants (17 female, 13 male; age: 44.2±8.3 years) was performed to evaluate the properties of a newly developed water-in-oil (W/O) balm on artificial sodium dodecyl sulfate-damaged epidermal barrier. The balm was applied 14 days twice daily, and transepidermal water loss and erythema were investigated. A significant improvement of both parameters after 12 days and even after 21 days could be confirmed. Two major clinical trials were performed to evaluate the safety and efficacy regarding protective and regenerative properties of the W/O balm on irritated skin in the anogenital area. Therefore, 29 children were enrolled (14 male, 15 female, age: 15.5±7.8 months) in an open-labeled 4-week clinical study. The balm was used in the area under disposable diapers at least after diaper change or if required. Furthermore, in a second open, multicenter study, 43 women (mean age: 46.2±16.9) with predisposition to skin irritation in the outer anogenital region were included. The product was applied for 4 weeks 1–2 times daily. In both studies, skin tolerability, applicability, scent, spreadability, and removability of the balm were evaluated by participants and practitioners predominantly as good or even very good, also skin hydration, protection, and regeneration were judged positively. The studies confirmed that the newly developed W/O balm exhibits excellent tolerability and is easy to remove. At the same time, excellent properties with respect to efficacy regarding regeneration and protection could be observed, without any undesired effects at any time. Keywords: intimate care, diaper rash, dermatitis, epidermal barrier